Hip and Knee Joint Angles Determine Fatigue Onset during Quadriceps Neuromuscular Electrical Stimulation - Jonathan Galvão Tenório Cavalcante; Álvaro de Almeida Ventura; Leandro Gomes de Jesus Ferreira; Alessandra Martins Melo de Sousa; Ivo Vieira de Sousa Neto; Rita de Cássia Marqueti; Nicolas Babault; João Luiz Quagliotti Durigan (Applied Bionics and Biomechanics, 2022)
Neuromuscular electrical stimulation (NMES) has been used to increase muscle strength and physical function. However, NMES induces rapid fatigue, limiting its application. To date, the effect of quadriceps femoris (QF) muscle length by knee and hip joint manipulation on NMES-induced contraction fatigability is not clear. We aimed to quantify the effects of different muscle lengths on NMES-induced contraction fatigability, fatigue index, and electromyographic (EMG) activity for QF muscle. QF maximum evoked contraction (QMEC) was applied in a 26 min protocol (10 s on; 120 s off; 12 contractions) in 20 healthy participants (24.0±4.6 years old), over 4 sessions on different days to test different conditions. The tested conditions were as follows: supine with knee flexion of 60° (SUP60), seated with knee flexion of 60° (SIT60), supine with knee flexion of 20° (SUP20), and seated with knee flexion of 20° (SIT20). Contraction fatigability (torque decline assessed by maximal voluntary contraction [MVC] and during NMES), fatigue index (percentage reduction in MVC), and EMG activity (root mean square [RMS] and median frequency) of the superficial QF’ constituents were assessed. After NMES, all positions except SUP20 had an absolute reduction in MVC (p<.001). Fatigue index was greater in SIT20 than in SIT60 (p<.001) and SUP20 (p=.01). There was significant torque reduction across the 12 QMEC in SUP60 and SIT60, up to 10.5% (p<.001–.005) and 9.49% (p<.001–.033), respectively. There was no torque reduction during NMES in SUP20 and SIT20. Fatigue was accompanied by an increase in RMS (p=.032) and a decrease in median frequency for SUP60 (p<.001). Median frequency increased only in the SUP20 condition (p=.021). We concluded that QF NMES-induced contraction fatigability is greater when the knee is flexed at 60° compared to 20°. In addition, a supine position promotes earlier fatigue for a 60° knee flexion, but it delays fatigue onset for a 20° knee flexion compared to the seated position. These results provide a rationale for lower limb positioning during NMES, which depends on training objectives, e.g., strengthening or task-specific functionality training.